Recent Advances in Real Options Signaling Games - Rigopoulos, George (The Asian Journal of Technology Management (AJTM), 2014)
Financial economics have benefited from game theory advances and its application to various domains where competition is present. Following relevant research this paper presents a literature review of recent works on the intersection of real options and game theory, especially on signaling games. A preliminary background is presented initially and next a review of the works is presented. The paper compiles existing works to a useful reference for researchers in the field. Keywords: Signaling games; Capital budgeting, Real options, Game theory, Discrete time games